Complement Activation and Prognosis in Patients With Type 2 Diabetes and Myocardial Infarction: A report from the DIGAMI 2 trial - Mellbin, Linda G. (American Diabetes Association, 2012)
OBJECTIVE: The activation of the complement system may be involved in the pathology of myocardial infarction (MI) and type 2 diabetes. To explore their potential as prognostic markers, we characterized two factors in the complement cascade, the end product sC5b-9 and the mannose-binding lectin–associated Ser protease-2 (MASP-2), in type 2 diabetic patients with suspected MI. RESEARCH DESIGN AND METHODS: Plasma sC5b-9 and MASP-2 were determined in patients with MI and type 2 diabetes (n = 397; median age 70; male 68%). The adjudicated end points were cardiovascular events (CVEs), including cardiovascular mortality and nonfatal MI or stroke. RESULTS: The median sC5b-9 was 134 μg/L (interquartile range [IQR] 101–190 μg/L) and the median MASP-2 was 333 μg/L (IQR 235–463 μg/L), with no significant correlation between them. Women had higher sC5b-9 than men (median 152 vs. 130 μg/L; P = 0.02). Both sC5b-9 and MASP-2 were correlated to age and creatinine clearance, while MASP-2 was also correlated to BMI. During a median follow-up of 2.4 years, CVEs occurred in 141 patients (36%). Both sC5b-9 (hazard ratio 1.37 [95% CI 1.13–1.65]; P < 0.01) and MASP-2 (0.68 [0.51–0.92]; P = 0.01) predicted CVEs in unadjusted analyses. After multiple adjustments, the predictive capacity remained for sC5b-9 (1.30 [1.02–1.66]; P = 0.04) but not for MASP-2. CONCLUSIONS: In type 2 diabetic patients with MI, high levels of sC5b-9 predict future CVE. This indicates that the complement system may play a significant role in the pathology of the subsequent myocardial damage and that the pathways leading to complement activation warrant further exploration as potential therapeutic targets to improve the prognosis for these patients.